A taxonomic review of Korean Acrotona Thomson with a description of new species (Coleoptera, Staphylinidae, Aleocharinae) - Lee, Seung-Gyu; Ahn, Kee-Jeong (Zootaxa, 2018)
A taxonomic review of the Acrotona Thomson in the Korean Peninsula is presented. The genus is represented in Korea by seven species including a new species, Acrotona (Acrotona) koreana Lee & Ahn, sp. nov. Two new synonyms are proposed: A. (A.) lutulenta (Sharp) = A. (A.) suyangsani Paśnik syn. nov., A. (A.) pseudotenera (Cameron) = A. (A.) paeksongricus Paśnik syn. nov. Three species [A. (A.) lutulenta (Sharp), A. (A.) pseudotenera (Cameron) and A. (A.) vicaria (Kraatz)] are reported for the first time in South Korea. A key, descriptions, habitus photographs and illustrations of the diagnostic characters are provided.